2021
DOI: 10.1016/j.ijid.2021.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Increasing smear positive tuberculosis detection using a clinical score – A stepped wedge multicenter trial from Africa

Abstract: Background: The Bandim TBscore is a clinical score that predicts treatment outcome in Tuberculosis (TB) patients and proved useful as an indicator of which healthcare-seeking adults to refer for sputum smear microcopy. We aimed to test in a randomized trial if the TBscore could be used to enhance the detection of smear positive (SP) TB. Methods: We carried out a stepped wedge cluster-randomized trial at six health centers in Bissau, Guinea-Bissau, and Gondar, Ethiopia. The primary outcome was diagnostic yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…On single outcomes by cascade, 11 (12.2%) studies reported TB testing outcomes[28][29][30][31][32][33][34][35][36][37][38], 22 (23.9%) reported TB diagnosis[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57], 15 (16.3%) reported on linkage to care[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74], 21 (22.8%) studies reported treatment completion[11,12,[75][76]...…”
mentioning
confidence: 99%
“…On single outcomes by cascade, 11 (12.2%) studies reported TB testing outcomes[28][29][30][31][32][33][34][35][36][37][38], 22 (23.9%) reported TB diagnosis[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57], 15 (16.3%) reported on linkage to care[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74], 21 (22.8%) studies reported treatment completion[11,12,[75][76]...…”
mentioning
confidence: 99%
“…The Bandim TBscore is a clinical score that predicts treatment outcome in TB patients and may prove useful as an indicator of which healthcare-seeking adults to refer for sputum smear microcopy. Rudolf et al (2021) conducted a stepped wedge cluster-randomized trial at six health centers in Bissau, Guinea-Bissau, and Gondar, Ethiopia. They conclude that it is an implementable approach and solution to an old and yet unresolved challenge.…”
mentioning
confidence: 99%